PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus di Desa Se-kecamatan Adonara Barat Kabupaten Flores Timur) - Suban, Albertus Satria Libu; Soleiman, Iriany Dewi (Program Studi Akuntansi Universitas Flores, 2022)
The purpose of this study was to determine the effect of applying government accounting standards and accounting information systems on the quality of village financial reports. The population in this study were all village officials in West Adonara District, East Flores Regency, totaling 32 people consisting of the Village Head, Village Secretary, Village Treasurer and Head of Finance. The sampling technique in this study used a saturated sampling technique. Saturated sampling is a sampling technique if all members of the population are used as samples. The sample in this study were all village officials in villages in the Adonara Barat District, East Flores Regency, totaling 32 respondents. This type of research uses quantitative research. This study uses primary data, namely a questionnaire. Data were analyzed using multiple linear regression analysis which was processed using IBM SPSS Statistics ver 25. The results of this study indicate that: (1) Government accounting standards affect the quality of financial reports. This is evidenced by the variable coefficient value of government accounting standards of 0.497 with tcount > ttable (6.121 > 2.045) and a significant level of 0.000 <0.05. (2) Accounting information systems affect the quality of financial reports. This is evidenced by the coefficient value of the technology utilization variable of 0.268 with tcount > ttable (2.154 > 2.045) and a significant level of 0.040 <0.05. Simultaneously the variables of government accounting standards and accounting information systems affect the quality of financial reports by 64.5% while the remaining 35.5% are influenced by other variables not explained in this study.